Segurança alimentar e a FAO: análise teórica e política externa brasileira (1994-2014) - (:unkn) unknown (UNIFAP - Universidade Federal do Amapá)
The existence of famine is as old as the own humankind history, which obliged the searching for innovations in order to overcome it. This bachelor thesis is concerned about analyze a concept that underlies the fight against hunger and the challenges to surmount it the food security concept. We also want to analyze the construction of this concept trough the International Relations field of study observing the Food and Agriculture Organization (FAO) influence regarding the improvements in the approaches related to this concept. A historical, theoretical, conceptual and practical perspective will be used to make this analysis. Trough an innovative approach, it will be used theoretical references from the. International Relations theories to analyze both the FAO actions and the Brazilian knowledge developed inside this subject. We'll also use a conceptual and practical analysis of the Brazilian Foreign Policy in a twenty years timeframe (1994-2014) in order to observe the Brazilian diplomacy influence towards the internationalization of this national knowledge as well as the speeches, concepts, actors and interests behind this promotion process of the Brazilian expertise to light against bung, er and the food security concept
Keywords: Organização das Nações Unidas para Alimentação e Agricultura (FAO); Relações internacionais; Política alimentar; Segurança alimentar; Política externa brasileira; CNPQ::CIENCIAS HUMANAS::CIENCIA POLITICA::POLITICA INTERNACIONAL::POLITICA EXTERNA DO BRASIL